Universal modesty in signal-burying games. Issue 1906 (3rd July 2019) - Quillien, Tadeg
Abstract : Why would individuals hide positive information about themselves? Evolutionary game theorists have recently developed the signal-burying game as a simple model to shed light on this puzzle. They have shown that the game has an equilibrium where some agents are better off deliberately reducing the visibility of the signal by which they broadcast their positive traits. However, this equilibrium also features individuals who fully broadcast their positive traits. Here, we show that the signal-burying framework can also explain modesty norms that everyone adheres to: the game contains an equilibrium where all agents who send a signal voluntarily reduce its conspicuousness. Surprisingly, the stability of the two kinds of equilibria rely on very different principles. The equilibrium where some agents brag is stable because of costly signalling dynamics. By contrast, the universal modesty equilibrium exists because buried signals contain probabilistic information about a sender's type, and receivers make optimal use of this information. In the latter equilibrium, burying a signal can be understood as a handicap which makes the signal more honest, but honesty is not achieved through standard costly signalling dynamics.